Motivasi Kerja sebagai Mediasi : Pengaruh Kompensasi Finansial dan Pengembangan Karyawan terhadap Kepuasan Kerja - Devi, I Gusti Ayu Marchika; Yuliana, Ika; Makiah, Makiah; Cahyadi, Irwan; Marlini, Febria Nurmelia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Employee satisfaction is a crucial factor in sustaining cooperative performance, particularly in organizations where human resources represent the core asset. However, inconsistencies in prior studies regarding the effect of financial compensation and employee development on job satisfaction indicate the need for further investigation. This study aims to analyze the influence of financial compensation and employee development on job satisfaction, with work motivation as a mediating variable. A quantitative associative approach was applied, using a saturated sampling technique involving 40 employees of Koperasi Simpan Pinjam Triananda Sari Utama. Data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS. The results reveal that financial compensation and employee development significantly and positively affect job satisfaction. Employee development also has a significant positive impact on work motivation. However, work motivation does not significantly influence job satisfaction and fails to mediate the relationship between the independent and dependent variables. These findings suggest that, in the cooperative context, job satisfaction is more directly determined by compensation and development rather than by motivational mechanisms. The study highlights the importance of strengthening compensation systems and employee development programs while exploring additional factors that may enhance both motivation and job satisfaction.